Assessment anti-granuloma activity of Alpha-lipoic acid in chicks’ models - Abdul-Ghani, MR; Naser, AS (Journal of the Hellenic Veterinary Medical Society, 2023)
Background: Alpha-lipoic acid is an anti-inflammatory and antioxidant agent that has free radical scavenging characteristics as well as better effects on the recycling of other cellular antioxidants. Aim: The present study was made to assess the anti-granuloma of Alpha-lipoic acid by the cotton pellet granuloma method. Method: The chicks weighing around 100-150 g were selected, the Alpha-lipoic acid was administered at the following dose of 20, 40 & 80 mg/kg body weight respectively after insertion of cotton pellets into the groin region of chicks. Results: By using the up-and-down technique, it was found that the Median Lethal Dose (LD50) of the Alpha-lipoic acid was 451.8mg/kg, IP. Alpha-lipoic acid at 20, 40, and 80 mg/kg per body weight daily for consecutive seven days revealed that the ALA shows dose-dependent inhibition of weight of both wet and dry cotton pellets. The inhibition percentage for wet cotton pellets was 5, 11, and 14 respectively whereas the inhibition percentage for dry cotton pellets was 9, 15, and 25 respectively. Conclusion: We conclude that Alpha-lipoic acid has notable anti-granuloma activity as compared to control in animal models of chronic inflammation. Additional studies must be done to find the molecular role of Alpha-lipoic acid as anti-granuloma remedies